Modified Tung Oil and Its Application in Oil-Contaminated Water Treatment - Dung, Le Van; Viet, Nguyen Thi Bich; Mai, Le Thi Thanh; Ngoc, Nguyen Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 4, 2016)
Abstract: